2017
DOI: 10.7150/jca.18073
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of the Expression Profile of Long Non-Coding RNAs Indicates lncRNA RP11-263F15.1 as a Biomarker for Diagnosis and Prognostic Prediction of Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a devastating malignancy with poor prognostic outcomes. Accumulating evidence has demonstrated that long non-coding RNAs (lncRNAs) play an important role in the development and progression of carcinogenesis. Nevertheless, little is known about the role of lncRNAs in PDAC. The aim of the current study was to find differentially expressed lncRNAs and related mRNAs in human PDAC tissues and adjacent normal tissues by microarray analysis, and investigate the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Several studies have demonstrated that lncRNAs are major regulators of gene expression and essential in a variety of pathological procedures, including cancer, cardiovascular diseases and neuronal disorders (22)(23)(24)(25). In addition, the expression profiles of lncRNAs are altered in cancer (26,27). The role and therapeutic potential of cancer-related lncRNAs have become a research hotspot in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that lncRNAs are major regulators of gene expression and essential in a variety of pathological procedures, including cancer, cardiovascular diseases and neuronal disorders (22)(23)(24)(25). In addition, the expression profiles of lncRNAs are altered in cancer (26,27). The role and therapeutic potential of cancer-related lncRNAs have become a research hotspot in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…A panel contains 8 circulating lncRNAs might be beneficial for early prediction of pancreatic cancer . Microarray analysis revealed that a single lncRNA (RP11‐263F15.1) might be useful in the diagnosis and prognostic of PDAC . Due to a large number of lncRNAs in the genome, we believed that some important lncRNAs in PDAC development are still undetermined, and more comprehensive studies should be taken to truly discover novel lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…28 Microarray analysis revealed that a single lncRNA (RP11-263F15.1) might be useful in the diagnosis and prognostic of PDAC. 29 Due to a large number of lncRNAs in the genome, we believed that some important lncRNAs in PDAC development are still undetermined, and more comprehensive studies should be taken to truly discover novel lncRNAs. Here, by mining the cancer genome atlas (TCGA) data set, we uncovered 8 novel lncRNAs that might be important in PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…However RT-qPCR has also some limitations such as: the amplicon size cannot be detected; maximum of four lncRNAs can be detected simultaneously; and non-specific binding can occur if SYBR ® green is used, among others [ 93 ] . Another technique commonly used to identify lncRNAs are microarrays [ 94 , 95 ] , which consist of a library of DNA specific sequences (known as probes) immobilized in a grid. The isolated mRNA is reversed transcribed into cDNA incorporating fluorescent probes and hybridized to the microarray.…”
Section: Technologies For the Isolation And Detection Of Exosomal Lon...mentioning
confidence: 99%